The Sustainable Social Responsibility and its Role in Promoting an Entrepreneurial Culture Applied on Egyptian Governmental Universities - Hosney, Mohamed (The Arab Journal of Administration, 2023)
Universities represent one of the main pillars of building civilization and developing societies. In recent years, the traditional view of Egyptian public universities has changed from mere institutions to granting higher degrees to a modern view in which these universities are considered an effective partner in achieving sustainable development Egypt vision 2030. Hence, in line with the realization of this vision, public universities had to contribute effectively to society’s issues, so the concept of sustainable social responsibility has emerged to express universities’ interest in their external environment side by side with their interest in their internal environment, and to achieve this concept has increased interest in the field of entrepreneurship, especially in Universities, given its contribution to creating new job opportunities and creating a generation of entrepreneurs that contribute to achieving sustainable development. From the above, the research aims to identify the reality of sustainable social responsibility at the level of public universities and its role in promoting a culture of entrepreneurship, and to achieve this goal, 380 survey forms were distributed electronically and on paper to a random sample of faculty members and the assisting body in different Egyptian government universities. The study found that there is a distinct lack of interest in the culture of entrepreneurship as a result of a lack of a sustainable social responsibility aspect in Egyptian government universities. The study concluded with a set of proposed recommendations in the form of an action plan to support and operationalize sustainable social responsibility practices in order to enhance the culture of entrepreneurship.